Olof Palme: One Life, Many Readings - Monica Quirico (Nordicum-Mediterraneum, 2011)
he aim of this article is not only to review the latest three biographies of Olof Palme, - written respectively by Kjell Östberg (2007-9), Klas Eklund (2010) and Henrik Berggren (2010) - but also and above all to identify their methodology, so as to single out some of the controversial points in Palme’s political career, yet leaving out both scandals and vulgar attacks.